Effect of Preoperative Nursing Visitation on Perioperative Anxiety, Intra/Post Operative, Nausea, Vomiting and Postoperative Pain in Surgical Patients Electives with Spinal Anesthesia - Agus Jatmiko; Joko Prasetyo; Ratna Wardani (STRADA : Jurnal Ilmiah Kesehatan, 2025)
The perioperative process can cause stress and anxiety of the patient which triggers negative physiological changes. Lack of information and therapeutic relationships between nurses and patients can worsen emotional responses. The purpose of the study was to determine the effect of preoperative nursing visitation on perioperative anxiety, IONV/PONV, and postoperative pain in elective surgery patients undergoing spinal anesthesia. The research design was a Quasi Experimental Pretest Posttest Nonequivalent Control Group with Block Random Allocation.